Survey on Sildenafil, Tadalafil, and Vardenafil Concentrations in Food Supplements for Erectile Dysfunction - Elina Petkova-Gueorguieva; Stanislav Gueorguiev; Hristina Lebanova; Vasil Madzharov; Anna Mihaylova (International Journal of Analytical Chemistry)
The aim of the study was to analyze the presence of undeclared sildenafil, tadalafil, and vardenafil in food supplements (FSs) for erectile dysfunction. The presence of sildenafil, tadalafil, and vardenafil was determined using the generated ultraviolet (UV)-spectra and mass-spectrometry (MS)-spectra as well as chromatograms produced by the photodiode array (PDA)-detector and ion trap MS-detector. The results were processed by Xcalibur ver. 2.0.7. Fourteen of the 20 analyzed FSs contained undeclared ingredients. Sildenafil was present in 12 of them. Many violations and discrepancies between the label information and the real composition of the FS were identified. 70% of the samples contained undeclared ingredients of an erectile dysfunction medicinal product. The quantities varied within broad limits from 2 mg per tablet to 116.55 mg per tablet. Sildenafil was present in amounts exceeding 16.55 mg that is the maximum recommended dose, thus creating risk of overdose. Besides that, food supplements adulterated with sildenafil analogues are a health risk for consumer’s health as there is no evidence of modified sildenafil toxicity. All analyzed FSs were claimed to be 100% natural, not provoking side effects. No information for any FS contained indications of age limits or risk for interaction with other FSs or medical products.